Intrapersonal Conflict Resolution Mechanisms in Women with High Trait Shame: A Qualitative Study - Acar, Zeynep; Kareem, Rana (Psychology of Woman Journal, 2025)
Objective: This study aimed to explore the intrapersonal conflict resolution mechanisms employed by women with high trait shame through a qualitative lens.Methods and Materials: A qualitative phenomenological research design was employed to investigate the lived experiences of 21 women residing in Georgia who reported persistently high levels of trait shame. Participants were recruited using purposive sampling, and data collection continued until theoretical saturation was achieved. Semi-structured, in-depth interviews were conducted to gather detailed personal narratives. All interviews were audio-recorded, transcribed verbatim, and analyzed using Braun and Clarke’s thematic analysis approach with the support of NVivo 14 software. Trustworthiness of the data was ensured through member checking, peer debriefing, and audit trails.Findings: Thematic analysis revealed four major categories of intrapersonal conflict resolution: (1) Emotional Regulation Strategies, including suppression, self-soothing, and distraction; (2) Cognitive Coping Mechanisms, such as rationalization, self-criticism, and identity negotiation; (3) Intrapersonal Dialogue and Reflection, encompassing internalized parental voices, dual-self conversations, and self-compassion struggles; and (4) Interpersonal Withdrawal and Boundary Dynamics, characterized by emotional isolation, fear of vulnerability, and covert boundary-setting. Participants often demonstrated complex internal negotiations, marked by inner conflict, shame resilience attempts, and reflective awareness. The findings align with existing literature on shame, psychological distress, and gendered identity development.Conclusion: These findings highlight the importance of therapeutic interventions that foster self-compassion, emotional awareness, and identity integration. Understanding these mechanisms provides critical insight into the internal lives of shame-affected women and offers a foundation for culturally informed mental health support.